استخدام برمجة (DeNovo) لتطوير شبكة المياه في استراتيجيات القرار المتعدد - بطيخ, عباس حسين; البدري, فاتن فاروق; علوان, فارس مهدي (Journal of Economics and Administrative Sciences, 2007)
The object of this study is to establish a global model to use of DeNovo programming the strategies of multi-Decision making process in the city of Baghdad.Thus, we have chosen an important and an effective subject in the life of the citizen due to the importance of this subject in the Iraqi citizen of luck of water and for many reasons.In this thesis, we have tackled the establishment of a global model to be able to reach solution or an alternative model a money the available alternative.        The alternative proposed here utilizes the application of the (DeNovo) programming approach suggested by (1982) in solving the capacity allocation problem. Unlike the usual optimization using mathematical models where level of resource, the right hand side of the assumed to be fixed or known, the (DeNovo) approach considers the level of resources as being decision variables that affect the value of the objective function.